2018
DOI: 10.1111/ijd.14197
|View full text |Cite
|
Sign up to set email alerts
|

Levels of miR‐31 and its target genes in dermal mesenchymal cells of patients with psoriasis

Abstract: Our results suggest that the low expression of miR-31 in DMSCs in patients with psoriasis causes an increase in the expression of some of its target genes, which in turn facilitates T lymphocyte activation by inhibiting the proliferation of DMSCs and therefore participates in the pathogenesis of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This is supported in transcriptomics by the involvement of proangiogenetic genes which are already expressed in non-lesional psoriatic skin [174]. Dermal mesenchymal stem cells are discussed as potential contributors in regulating angiogenesis in the skin [175][176][177][178]. In addition, anti-TNFα treatment led to the upregulation of VEGF negative regulating pathways [179].…”
Section: Dcsmentioning
confidence: 93%
“…This is supported in transcriptomics by the involvement of proangiogenetic genes which are already expressed in non-lesional psoriatic skin [174]. Dermal mesenchymal stem cells are discussed as potential contributors in regulating angiogenesis in the skin [175][176][177][178]. In addition, anti-TNFα treatment led to the upregulation of VEGF negative regulating pathways [179].…”
Section: Dcsmentioning
confidence: 93%
“…In PsA patients, serum complement component 3 (C3) levels were reported higher than in control group 22 . Since prolargin has previously been shown to inhibit the alternative pathway C3 convertase 21 , and its expression to be 1.35-fold higher in psoriasis group compared to controls in miR-31 microarray assay 23 , it is likely relevant to PsA as well. Indeed, prolargin was recently suggested as a new protein candidate indicative of response to anti-tumor necrosis factor (TNF)-α in PsA, thus warranting further investigation of this protein in this disease 24 .…”
Section: Introductionmentioning
confidence: 99%
“…We observed that MSCs from the skin showed an immunophenotype that was similar to that of BM-MSCs because there were no statistically significant differences in the expression levels of the markers that were analyzed, except in the expression of HLA-I, whose relevance will be discussed later. Previous studies have described the presence of MSCs in the dermis derived from healthy donors and patients with psoriasis, although in some cases, a complete characterization has not been performed [23]. For example, a previous study reported the presence of multipotential mesenchymal stem cells in the foreskin but did not determine the expression of CD73, HLA-I, or HLA-II or the chondrogenic differentiation capacity of the cells [24].…”
Section: Discussionmentioning
confidence: 99%